2017
DOI: 10.3389/feart.2017.00106
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Dissolved Organic Matter Reactivity in Lake Water

Abstract: Lakes in the boreal region have been recognized as the biogeochemical hotspots, yet many questions regarding the regulators of organic matter processing in these systems remain open. Molecular composition can be an important determinant of dissolved organic matter (DOM) fate in freshwater systems, but many aspects of this relationship remain unclear due to the complexity of DOM and its interactions in the natural environment. Here, we combine ultrahigh resolution mass spectrometry (FT-ICR-MS) with kinetic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 93 publications
5
72
0
Order By: Relevance
“…In agreement with the loss of fluorescence the degree of aromaticity was lost on the first view (Table S7). The double bond equivalence (DBE) decreased as expected [9,80,81]. Nitrogen remains constant, carbon and oxygen decreased and sulphur increased, mostly from t = 10 (168 kW/m 2 cumRAD, second important drop).…”
Section: Average Photo-chemical Dom Quality Changesupporting
confidence: 55%
See 1 more Smart Citation
“…In agreement with the loss of fluorescence the degree of aromaticity was lost on the first view (Table S7). The double bond equivalence (DBE) decreased as expected [9,80,81]. Nitrogen remains constant, carbon and oxygen decreased and sulphur increased, mostly from t = 10 (168 kW/m 2 cumRAD, second important drop).…”
Section: Average Photo-chemical Dom Quality Changesupporting
confidence: 55%
“…In total, there was a decrease of 50% for peak B (ex: 320 to 400 nm; em: 380 to 500 nm) and of 75% for peak A (ex: 240 to 280 nm; em: 380 to 500 nm). These two peaks were also relevant in [81] or [85], where they also decreased under UV irradiation. This means that also the fDOM was reduced, more than the chromophoric DOM.…”
Section: Identification Of Dom Quality Changes With Eems Suva and Thmentioning
confidence: 76%
“…In support of this, recent work at the molecular level has highlighted that not all aromatic DOM is resistant to degradation (Mostovaya et al. ). Finally, positive relationships between aquatic CO 2 and NH 4 have been reported elsewhere (Schrier‐Uijl et al.…”
Section: Discussionmentioning
confidence: 91%
“…Positive correlations between dissolved CO 2 and SUVA have been observed for small peatland pools and ditches (Turner et al 2016, Peacock et al 2017, and could suggest that DOM with higher molecular weight or increasing aromaticity is more bioavailable to aquatic microbial communities (Tranvik 1990). In support of this, recent work at the molecular level has highlighted that not all aromatic DOM is resistant to degradation (Mostovaya et al 2017). Finally, positive relationships between aquatic CO 2 and NH 4 have been reported elsewhere (Schrier-Uijl et al 2011, Yu et al 2017.…”
Section: Concentrations and Fluxes Of Comentioning
confidence: 92%
“…Aliphatic, N‐containing, and S‐containing compounds detected by FT‐ICR MS have been linked to chlorophyll a (Osterholz et al ), a proxy for primary production. Aliphatic compounds have also been found to be particularly susceptible to microbial degradation, although microbial degradation has been linked to the loss of a variety of molecular formulae (D'Andrilli et al ; Spencer et al ; Mostovaya et al ). The relative abundance comprised by aliphatic compounds in the current study was lower than previously observed in lakes and rivers (Wagner et al ; Kellerman et al ).…”
Section: Discussionmentioning
confidence: 99%